PRINCIPLES OF MARKETING FROM AN ISLAMIC PERSPECTIVE - Ahmad, Khaliq (Journal of Islamic Management Studies, 2022)
This is a book review not normal article. Hence no abstract rather the title and authors are as follows: Principles of Marketing from An Islamic Perspective Authored by Ahasanul Haque, Nurhazirah Hashim, Ali Shafiq, (2021) INTHOUGHT, International Institute of Islamic Thought/IIUM, 2021. ISBN:9789674454876. RM 16 (e-copy price excluding 0% GST) Reviewed by Professor Khaliq Ahmad, ISTAC, International Islamic University Malaysia, Kuala Lumpur Campus, Malaysia.